The dynamical diquark model: fine structure and isospin - Jesse F. Giron; Richard F. Lebed; Curtis T. Peterson (Journal of High Energy Physics)
Abstract We incorporate fine-structure corrections into the dynamical diquark model of multiquark exotic hadrons. These improvements include effects due to finite diquark size, spin-spin couplings within the diquarks, and most significantly, isospin-dependent couplings in the form of pionlike exchanges assumed to occur between the light quarks within the diquarks. Using a simplified two-parameter interaction Hamiltonian, we obtain fits in which the isoscalar JPC = 1++ state — identified as the X (3872) — appears naturally as the lightest exotic (including all states that are predicted by the model but have not yet been observed), while the closed-charm decays of Zc(3900) and Zc(4020) prefer J/𝜓 and hc modes, respectively, in accord with experiment. We explore implications of this model for the excited tetraquark multiplets and the pentaquarks.